Preferred leadership style, managerial and entrepreneurial inclination among Hungarian students - Éva Perpék; Ágnes Gyîori; György Lengyel (Journal of Innovation and Entrepreneurship, 2021)
Although a great deal of research has been done on leadership styles, and university students have often been the subject of exploratory research in social sciences, the Full Range Leadership model has been applied to young people only in a few instances. In this article, the authors seek to survey the preferred leadership styles among Hungarian students and explore how they correlate with managerial and entrepreneurial inclination. A complex analysis of leadership style preferences of university students combined with their managerial and entrepreneurial inclination, social and cultural resources is rare in the research practice so far. The online questionnaire used in the research was completed by 335 university students studying economics, engineering and social studies both in Budapest and in the country. The questionnaire was completed by 335 university students. The results are exploratory and they amend the existing leadership typologies at some points. Based on the results of the Multifactor Leadership Questionnaire featuring 36 self-rating items, four distinct leadership styles emerged within the target group, representing the transformational, the supportive, the defensive, and the laissez-faire leadership types. The multivariate analysis has shown that while managerial inclination is related to the transformational style of leadership, entrepreneurial aspirations are associated with the transformational and supportive leadership styles.
Keywords: 650; Leadership style; Transformational leadership; Managerial aspirations; Entrepreneurial inclination; University students